KORELASI KONSUMSI MAKRONUTRIEN DENGAN PROFIL LIPID PADA PETUGAS KESEHATAN YANG OBESITAS DI RSUP M. DJAMIL PADANG TAHUN 2022 - Juana, Aulia Luthfi Putri; Sy, Elmatris; Lipoeto, Nur Indrawati (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Dyslipidemia is a health problem that needs attention because the incidence of dyslipidemia in Indonesia continues to increase from year to year. Macronutrient intake in a diet can influence a person's lipid profile. This study aims to determine the correlation between macronutrient consumption in obese health workers at RSUP Dr. M. Djamil Padang in 2022.  This research is an analytical research with a cross sectional study design on secondary data from diet development research on health workers at RSUP Dr. M. Djamil Padang who is obese in 2022 with research subjects of 40 respondents taken using total sampling technique. Data analysis used univariate and bivariate analysis with the Pearson Spearman correlation test. Correlation is declared significant if p<0,05.  The research results showed that the highest mean macronutrient consumption was carbohydrates (219.92 ± 74.21), then fat (64.30 ± 28.35) and the lowest was protein (62.56 ± 18.74). Respondents also had lipid profile values that were in the normal range for total cholesterol (157.75 ± 51.58) and triglycerides (125.33 ± 33.21) and there was an increase in LDL (106.46 ± 40.13) and HDL ( 76.35 ± 27.54).  From this study it was concluded that there was a significant correlation between carbohydrate consumption and total cholesterol (p value = 0.026; r = 0.351) and LDL (p value = 0.008; r = 0.415), but there was no correlation between carbohydrates, protein and fat with the profile other lipids in obese health workers at RSUP Dr. M. Djamil Padang.